The unmet supportive care needs, quality of life, and care experiences of patients with functioning and non-functioning Neuroendocrine tumours (NETs) at early diagnosis. Issue 1 (January 2022) - Guccione, Lisa; Gough, Karla; Drosdowsky, Allison; Price, Timothy; Pavlakis, Nick; Wyld, David; Ransom, David; Michael, Michael; Schofield, Penelope
Abstract: Objective: Healthcare experiences, quality of life and psychosocial needs of patients with Neuroendocrine tumours (NETs) will be assessed to identify differences between NET sub-groups and inform the design of supportive care services. Methods: This study constitutes phase one of a three-phase mixed-methods multi-site study with NET patients (n = 123). Demographic, clinical and patient reported outcome questionnaire data was collected. Results: No differences in patient reported outcomes were found beyond symptoms of diarrhoea and flushing between NET sub-groups. For combined NET patients, the majority reported negative experiences in their understanding of the explanation of what was wrong with them (67%); receiving written information about their cancer (69%), their family/carer receiving all the information required to care for them (61%); and the usefulness of information about NETs online (66%). NET patients reported at least one moderate-to-high need for disease specific information (63%). Medium- to large-sized differences in quality of life subscales were also observed with the functioning group reporting more anxiety compared to population norms. Conclusions: There is a need to improve the current provision of information for people with NETs. Practice implications: These findings will inform the design and development of an informational resource to facilitate improved understanding for patients with NETs. Highlights: Both functioning and non-functioning NET patients report reduced quality of life to the general population. NET patients report a moderate-to high need for information about their disease, treatment options or disease management. NET patients report negative experiences in their ability to understand their disease as well as access useful information resources. There is a need to improve the current provision of information for people with NETs.